2019
DOI: 10.1080/20002297.2019.1653123
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis in saliva associates with chronic and aggressive periodontitis

Abstract: Objective: To characterize the salivary microbiota of patients with aggressive periodontitis, patients with chronica periodontitis and orally healthy individuals. Methods: A total of 81 unstimulated saliva samples from aggressive periodontitis patients (n = 31), chronic periodontitis patients (n = 25), and orally healthy controls (n = 25) were examined. The V1-V3 region of the 16S rDNA gene was sequenced with Illumina® MiSeq TM , and sequences were annotated to the expanded Human Oral Microbiome Database (eHOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 41 publications
6
43
1
1
Order By: Relevance
“…In this study, both of IL-1β and Pg showed signi cant difference among three groups, their salivary level were increasing in the gingivitis group and more higher in the periodontitis group. Our data were in consistence with other studies [12,19], and besides signi cant elevation in gingivitis and periodontitis groups, our data also demonstrated positively association of IL-1β and Pg with clinical indexes (PD and BOP), showed they indeed re ected the periodontal status and can be valuable candidates to predict periodontal disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, both of IL-1β and Pg showed signi cant difference among three groups, their salivary level were increasing in the gingivitis group and more higher in the periodontitis group. Our data were in consistence with other studies [12,19], and besides signi cant elevation in gingivitis and periodontitis groups, our data also demonstrated positively association of IL-1β and Pg with clinical indexes (PD and BOP), showed they indeed re ected the periodontal status and can be valuable candidates to predict periodontal disease.…”
Section: Discussionsupporting
confidence: 91%
“…We believe that the change of different markers occur no simultaneously but consecutively at different phase of periodontal disease, a biomarker combination can be more effectively used for diagnosing disease. Salivary interleukin (IL)-1β [9], matrix metalloproteinase (MMP)-8 [10], pyridinoline cross-linked carboxyterminal telopeptide of type I collagen (ICTP) [11] and Porphyromonas gingivalis (Pg) [12] were high prevalence in the populations and revealed a high relationship of periodontitis, the aim of this study is to evaluate discriminate e ciency of these markers among healthy, gingivitis and chronic periodontitis patients and pair them to build a prediction panel for diagnosing periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the majority of these bacterial species, including the proposed periopathogen P. gingivalis, were identified with higher relative abundance in patients with periodontitis. Salivary levels of P. gingivalis have been reported to associate with periodontitis (Damgaard et al, ), and previous studies have shown a positive correlation of salivary and subgingival levels of P. gingivalis (Belstrøm et al, ; Nickles, Scharf, Röllke, Dannewitz, & Eickholz, ) suggesting that the salivary microbiota reflects local bacterial alterations associated with periodontitis.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, several studies have aimed to differentiate patients with periodontitis from orally healthy controls by means of salivary levels of putative periopathogens. For example, a recently published NGSbased study showed that relative abundance of P. gingivalis could discriminate patients with periodontitis from orally healthy controls with an AUC (area under curve) of 0.80 [42], and a PCR-based study of 9 selected periopathogens reported that it was possible to discriminate the severity of periodontitis based on salivary levels of the bacteria tested [43]. Furthermore, salivary levels of periopathogens have been used in periodontal risk assessment.…”
Section: Periodontitismentioning
confidence: 99%